2019
DOI: 10.31235/osf.io/dn46x
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Implications of Online Translation Courses on Instructors’ Philosophy of Teaching

Abstract: The paper aims to shed more insights into the impact of online learning on the philosophy of teaching online translation courses. It starts from the premise that online translation courses have peculiar epistemological and pedagogical characteristics which differ from those available in conventional teaching settings. The traditional styles of teaching translation courses have generally focused on linguistic competence and translation and interpreting skills with a little focus on the increasing demands and ch… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The results showed a positive perception of 90% on the use of Omega and Google Classroom. Ismail et al (2019) studied the impact of OL on the philosophy of teaching online translation courses. They found that teachers' perception of online is influenced by their philosophy of OL.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed a positive perception of 90% on the use of Omega and Google Classroom. Ismail et al (2019) studied the impact of OL on the philosophy of teaching online translation courses. They found that teachers' perception of online is influenced by their philosophy of OL.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One-sample t-test was used to analyze Likert scale-based survey to detect a statistical significance in the distribution of the faculty's perception of online teaching of translation courses, which is recommended by De Winter and Dodou, (2010) and Harpe (2015). The survey consists of five points: strongly disagree, disagree, neutral, agree and strongly agree; thus, the t-test can indicate how five-point Likert data look like in a group (Ismail et al, 2019).…”
Section: Questionnaire Designmentioning
confidence: 99%